Classical Cornelia de Lange Syndrome - Badoe, EV (Ghana Medical Association, 2006)
These two case reports illustrate the importance of doing a thorough dysmorphology examination for all so called “Multiple congenital anomalies” children and attempting to fit them into a recognized syndrome. Well over 2000 dysmorphic syndromes are now recognized and diagnosis of these children can be extremely difficult.